2020
DOI: 10.3390/su12051719
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants behind the Acceptance of Autonomous Vehicles: A Systematic Review

Abstract: Excessive dependence on autonomous vehicles (AVs) may exacerbate traffic congestion and increase exhaust emissions in the future. The diffusion of AVs may be significantly affected by the public’s acceptance. A few factors that may affect people’s acceptance of AVs have been researched in the existing studies, one-third of which cited behavioral theories, while the rest did not. A total of seven factors with behavior theories are screened out that significantly affect the acceptance intention, including percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 239 publications
(113 citation statements)
references
References 127 publications
6
104
0
3
Order By: Relevance
“…Interestingly, in the case of level 3 AVs, it was reported that it was the ease of use which predicted the intention to use and not perceived usefulness [30]. All in all, it was the perceived usefulness which had most often the strongest influence on intention to use AVs [40].…”
Section: Technology Acceptance Modelmentioning
confidence: 98%
See 3 more Smart Citations
“…Interestingly, in the case of level 3 AVs, it was reported that it was the ease of use which predicted the intention to use and not perceived usefulness [30]. All in all, it was the perceived usefulness which had most often the strongest influence on intention to use AVs [40].…”
Section: Technology Acceptance Modelmentioning
confidence: 98%
“…Authors of AV's acceptance models often adapt the original models and incorporate novel factors. Among the most cited factors were respectively: perceived ease of use, perceived usefulness, trust, attitude, social norm, perceived risk and compatibility [40]. Such research is recently rapidly gaining in numbers (e.g.…”
Section: Acceptance Of Autonomous Vehiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the responses of the survey that follows support this notion of hesitance and the hybrid option of human-machine collaboration is currently a more acceptable choice. By training the AI system and updating the road network with the required infrastructure, fully autonomous versions could be required in the near future and will be further investigated [31].…”
Section: Proposed Solution: Ar/ai Systemmentioning
confidence: 99%